Understanding Evidence-Based Rheumatology A Guide to Interpreting Criteria, Drugs, Trials, Registries, and Ethics - Yazici, Hasan; Yazici, Yusuf; Lesaffre, Emmanuel (Springer International Publishing : Imprint: Springer, 2014)
It is imperative that health professionals caring for patients with rheumatic diseases understand how to correctly interpret evidence in their field, taking into account the merits and shortcomings of available data. Understanding Evidence-Based Rheumatology offers a practical assessment of criteria, drugs, trials, and registries and provides useful tools for successfully interpreting this data. The book introduces readers to basic analysis of trial design, statistics, and application of data through no-nonsense, easy-to-follow insights. Using numerous examples, chapters outline the difficulties physicians encounter when measuring disease activity in rheumatology, and offer strategies for systematically approaching these situations. Ethical issues in study design and reporting are examined, and the book closes with a summary of future directions for scientific and clinical studies in rheumatology. Understanding Evidence-Based Rheumatology is an invaluable resource for trainees, experienced clinicians, and scientists, preparing them with the necessary tools to correctly gather evidence and shed light on the difficult practice of rheumatology.  .